Fostering uncertainty in the law of tort (Armes v Nottinghamshire CC) - Dickinson, A (Sweet and Maxwell, 2018)
Discusses five elements of judicial reasoning in Armes v Nottinghamshire CC (SC), which found a council vicariously liable for the abuse suffered by the claimant at the hands of her foster parents, that may be open to criticism. Discusses the court's assessment of whether the features of an employment relationship existed, the unpredictability of the expanding scope of vicarious liability and its causal requirement, and the possible consequences.